Social gating of statistical learning in infants through interpersonal neural synchrony - Teo, Kai Xin (Nanyang Technological University, 2020)
Social interaction is important for infants’ learning as it provides various ostensive cues like infant-directed speech, eye-contact, and pointing, which guides infants’ attention resulting in learning. Infants are sensitive to eye-contact and previous research indicated that eye-contact plays a critical role in infants’ social learning. When infants and adults interact, there is an exchange of eye-contact. Past research has provided evidence that eye-contact can influence neural activities between an infant and an adult, bringing both brains to a phase of synchronization. However, it is not known whether interpersonal neural synchronization will influence statistical language learning, an innate mechanism that facilitates infants’ learning through the detection of regularities and patterns in sensory information. Thus, this study examined the effects of eye-contact (full, partial, or none) on neural synchrony and whether neural synchrony will affect infants’ statistical language learning. Infants of 8 to 10 months old (n = 18) were recruited and results showed that there were significant effects of eye- contact on neural synchrony (within-infant, within-adult, and infant-adult), but it was only found for within-infant synchrony in the full eye-contact condition. No significant findings were found between neural synchrony and statistical language learning. This demonstrates there are changes to neural activities in the infant's brain when full eye-contact is established, however the change in neural activities may not directly affect statistical learning. Instead, changes in neural activities indicate that eye-contact may act as an attentional cue that prepares the brain for the reception of information.